Evaluation of the effect of addition of polyester fiber on some mechanical properties of heat cure acrylic resin - Hachim, Thikra M; Abdullah, Zainab S; Alausi, Yasamin T (Journal of Baghdad College of Dentistry, 2013)
Background: This study aimed to evaluate the effect addition of polyester fibers on the some mechanical properties of heat cured acrylic resin (implant strength, flexural strength and hardness) Materials and methods: Ninety specimens were used in the study. Thirty specimens were used for impact strength measurements (80mm X 10mm X 4mm) length, width and thickness respectively. The specimens divided into three test groups (n=10), first group formed from heat cure acrylic resin without fiber reinforcement. Second group was formed from heat cure acrylic resin was reinforced with 2 mm length polyester fiber and third group was formed from heat cure acrylic resin reinforced with 4mm length polyester fiber, impact strength measured by impact testing device. 30 specimens with (65 mm X 10mm 2.5mm) length, width and thickness respectively were used in 3 groups (n=10) flexural strength test. The flexural strength was measured by using flexural testing device. 30 specimens with (65mm X 10m X 2.5mm) length width and thickness respectively were used for hardness test. The specimens were divided into 3 group (n=10) as in impact strength and flexural strength. Hardness measured by using (shore D hardness tester TH210). Results: revealed statistically significant increase on impact strength especially on 4mm length when compared to control group. Significant decreases in flexural strength of PMMP. When compared to control group with 4mm length fiber reinforcement. Non significant decrease when compared control group with 2mm length fiber reinforced PMMA. Significant decrease in hardness of PMMA resin after reinforcement with 2mm, 4mm lengths polyester fibers. Conclusions: Strengthening with the polyester fiber decreased the flexural strength and hardness of the resin, but increased impact strength. Thus when high impact acrylic resins are needed, fiber reinforced resins may be the material of choice.